Impact of Two Hexaploidizations on Distribution, Codon Bias, and Expression of Transcription Factors in Tomato Fruit Ripeness - Yating Han; Wanjie Hu; Xiuling Wu; Xinyu Li; Junxi Luo; Ziying Zhu; Zhenyi Wang; Ying Liu (Horticulturae)
Transcription factors play an important regulatory role in tomato fruit ripening. We identified and analyzed eight transcription factor families (TF families) associated with fruit ripening in the genomes of seven tomato species and two outgroup species, revealing the impact of whole-genome duplication (WGD) events on the structure and functional characteristics of these TF families. The results indicate that the Solanaceae Common Hexaploidization (SCH) event is the primary driver for the increase in the number of members within these TF families, leading to a more concentrated chromosomal distribution of family members. Compared with the two outgroup species, the tomato fruit-ripening-related TF families exhibit stronger codon usage bias, which may have been enhanced by WGD. Phylogenetic analysis found that family members generated by SCH show faster evolutionary rates, suggesting that SCH events significantly contribute to the evolution of these families. Additionally, our research uncovered that WGD events might maintain expression activity during fruit ripening by generating duplicate TF family members. Our study not only deepens our understanding of the mechanisms underlying tomato fruit ripening but also provides a theoretical foundation for future breeding improvements.